Timber roof trusses installation process, Pasar Paka, Dungun / Muhamad Arif Roslin - Roslin, Muhamad Arif (2016)
Industry Training is a main component in learning at Universiti Teknologi MARA (UiTM) and for every student who attended either a diploma or certificate courses. Students are required to pass the industrial training before they are certified for the award of the Certificate or Diploma. Students pursuing diploma courses will undergo their practical training in the sixth semester for 4 months and in addition, students are required to prepare a report based on the task of industrial training was conducted and performed during the industrial training.During practical training,the topic of the report based on scope of work for the company. Haustek Engineering as a company who undertaken the Industrilized building system which is prefabricated timber framing and block system. From my experience,I should to desribes about the IBS system.For the case study,I choose the renovation work for roof trusses at Pasar Paka,Dungun. The case study used prefabricated timber framing system,It included the IBS system.IBS system have a special method of contruction because there have good planning.In the report,I describes the process of the timber trusses start from design stage to installation stages.